Associations of HMGB1 gene polymorphisms with risk of coal workers' pneumoconiosis susceptibility in Chinese Han population. (20th March 2020) - Tang, Yijun; Duan, Jingzhu; Wang, Yun; Yuan, Leyong
Abstract: Background: High-mobility group box 1 (HMGB1) protein plays an important pathogenic role in various diseases such as pulmonary fibrosis. However, the relationship between variation of HMGB1 gene and susceptibility to coal worker's pneumoconiosis (CWP) remains unclear. The objective of the study was to determine the association between HMGB1 polymorphisms and CWP in Chinese Han population. Methods: The genotypes of HMGB1 gene rs1045411, rs2249825, rs1412125 and rs1360485 in 340 CWP patients and 312 healthy controls were determined and serum HMGB1 levels were detected. Results: Our finding showed that the HMGB1 rs1360485 G allele increased the risk of CWP in comparison with A allele ( P  = 0.005). HMGB1 rs1360485 GG genotype as well as AG+GG genotype increased the risk of CWP in comparison with AA genotype ( P  = 0.010, P  = 0.025, respectively). Four haplotypes were identified and we found that the GCTA haplotype was associated with resistance to CWP ( P  = 0.005), while GCTG haplotype was associated with risk to CWP ( P <0.001). Meanwhile, multifactor dimensionality reduction (MDR) analysis showed that the interaction between rs1360485 and exposure had the strongest, followed by rs2249825 and rs1412125. This study also found that the serum HMGB1 levels of the case group were significantly higher than that of the control group, and the serum HMGB1 levels of homozygous subjects with rs1360485 mutant were higher than that of the heterozygous wild type, respectively ( P <0.001). Meanwhile, the levels of HMGB1 with GCTA haplotype was lower than with GCTG haplotype ( P <0.001) Conclusion: Our findings indicated that HMGB1 gene rs1360485 polymorphism was associated with the susceptibility to CWP in Chinese Han population.